Mitigasi Resiko pada Perbankan Syariah di Indonesia - Naura, Debi; Syahpawi, Syahpawi; Syukri, Mahyudin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Financial institutions, especially sharia banking institutions, will always face various forms of risk with varying complexity and are inherent in business activities in their business. Therefore, it is very urgent to implement risk management in Islamic banking in order to identify, measure and control the various risks that will be faced. This research aims to examine the concept of risk management implemented in Indonesian sharia banking. The type of research carried out by researchers is library research by searching and collecting references that are relevant to the study topic. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The findings from this research are that the types of risks that are common in sharia banking consist of financing risk, liquidity risk, operational risk and market risk.